Strategic resources, a driver of performance in small and medium manufacturing enterprises in Kenya - Muturi Moses Murimi; Beatrice Elesani Ombaka; Joseph Muchiri (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: This study sought to establish the effect of strategic resources on performance of small and medium manufacturing enterprises. Specifically, the study sought to identify how financial resources, human resources, physical resources and intellectual capital affect performance of small and medium manufacturing enterprises in Kenya. Methodology: Positivism research philosophy was utilised. Cross-sectional descriptive survey as well as explanatory study design were used in the study. The target population for the study was 350 Kenyan SMEs in the manufacturing sector. A sample of 183 firms was selected using stratified random sampling. One respondent from each firm was selected being the managing director. Data was collected using a semi-structured questionnaire. Diagnostic tests for multicollinearity and normality were conducted before data analysis. The research questionnaire was tested for content validity and reliability after. Data was analysed using inferential and descriptive statistics. Data collected was analysed using SPSS V23. Finding: The study found that strategic resources have a significant influence on significant influence on performance of manufacturing SMEs in Kenya. Specifically, financial, human and physical resources all positively and significantly influenced the performance of Kenyan SMEs while intellectual resources as no effect on performance. The study therefore concluded that financial resources have a positive and significant influence on performance of manufacturing SMEs in Kenya, human resource was found to be significant in predicting performance. Physical resources have a significant influence on performance of manufacturing SMEs in Kenya while intellectual capital has no significant influence on performance of manufacturing SMEs in Kenya. Study Implication: The study recommended that Management of manufacturing SMEs should ensure that there are enough financial resources to meet their daily transactions and ensure that they are able to acquire the relevant strategic resources for efficient running of their firms; have adequate, committed and well-skilled personnel with the required expertise; should invest significantly in physical resources in order to maximise the performance of these firms; carry our cost benefit analysis before committing their resources to protect their intellectual capital in form of patents. Value of the Study: The study showcases the influence of strategic resources on performance of manufacturing SMEs in Kenya.
Keywords: M12; M10; M13; 330; Strategic Resources; Firm Performance; Resource Based View; Balanced Score Card Model; Small and Medium Manufacturing Enterprises